Molecular chaperone-like properties of sodium caseinate to suppress the pressure-induced aggregation of β-lactoglobulin. Issue 2 (3rd April 2019) - He, Jin-Song; Gao, Qing; Mu, Tai-Hua; Azuma, Norihiro
ABSTRACT: The objective of this study was to determine whether sodium caseinate can inhibit the aggregation of whey protein induced by pressure treatment. Solutions of β-lactoglobulin (β-Lg, 0.2%, w/v) and mixtures containing 0.2% (w/v) β-Lg and 0–0.5% (w/v) sodium caseinate (NaCas) were pressurized at 400–800 MPa. NaCas suppressed the aggregation of β-Lg induced by pressure treatment, and this function was dependent on the concentration of NaCas. Furthermore, NaCas altered the aggregation process of β-Lg by suppressing the transition of the aggregate from the soluble phase to the insoluble phase and, as a result, the fraction of insoluble aggregates was decreased. During this process, NaCas formed stable complexes with the denatured β-Lg, and the formation of complexes prevented further aggregation of β-Lg. These results indicate that NaCas exhibits a chaperone-like activity under high pressure.